Characterization and transfer of chloramphenicol resistance gene in bacteria isolated from aquaculture ponds - Abdul Rahman, Noor Azrin (2011)
The presence of antibiotic residues and antibiotic resistant organisms in agriculture and aquaculture environments and products constitute a potential threat to the sustainable development and international trade in the industries. A total of 127 chloramphenicol resistance isolates obtained from selected aquaculture ponds in Selangor and Perak, Malaysia, were tested their susceptibility to common antibiotic used in aquaculture by using the disk diffusion method and minimal inhibitory concentration. Most of the chloramphenicol resistant isolates were also highly resistant to nitrofurantoin (80.3%), trimethoprim/ sulfamethoxazole (78%) and tetracycline (74.8%). The minimal inhibitory concentration (MIC) analysis showed that most of the isolates were resistant to chloramphenicol at MIC value > 1024 ppm. The chloramphenicol resistance genes detection in the isolates using multiplex PCR assay shown that, two chloramphenicol resistant genes (cat I and cat II) were successfully amplified from 51 out of 127 isolates. The assay determined that cat II was the dominant gene occurring in 47 out of 127 isolates. Forty one of 76 isolates that did not carry positive cat genes, gave positive changes in biochemical cat assay. Of the 51 cat gene positive isolates, 35 (69%) isolates harbored plasmids. Among the 35 isolates, 21 were observed to harbor plasmid and susceptible to streptomycin (> 6mm to STR10μg disk) and possibility of chloramphenicol resistance gene transfer from these positive isolates to naive bacteria via conjugation were tested by using plate mating method. However, the transfer of chloramphenicol resistant gene was not clearly detected in any isolate.